A new class of silica-supported chromo-fluorogenic chemosensors for anion recognition based on a selenourea scaffold. Issue 26 (16th March 2017) - Casula, Arianna; Llopis-Lorente, Antoni; Garau, Alessandra; Isaia, Francesco; Kubicki, Maciej; Lippolis, Vito; Sancenón, Félix; Martínez-Máñez, Ramón; Owczarzak, Agata; Santi, Claudio; Andrea Scorciapino, M.; Caltagirone, Claudia
Abstract : The first example of a chromo-fluorogenic chemosensor containing a selenourea moiety is here described. Abstract : The first example of a chemosensor (L) containing a selenourea moiety is described here. L is able to colorimetrically sense the presence of CN − and S 2− in H2 O : MeCN (75 : 25, v/v). Moreover, when L is loaded into functionalised mesoporous silica nanoparticles an increase in the selectivity towards S 2− occurs via a selective fluorescence response.